Rethinking gharar in digital business subscriptions: A Sharia perspective on automatic renewal practices - Koswara, Asep; Herlina, Lina; Kurniawati, Neni (Journal of Islamic Law on Digital Economy and Business, 2026)
Purpose – This study aims to evaluate the Shariah compliance of automatic renewal mechanisms in digital subscription business models. It specifically investigates whether these practices align with Islamic legal principles, focusing on the potential presence of gharar (uncertainty) and its impact on consumer protection in the insurance industry. Methodology – This study employs a qualitative normative legal approach. It analyzes contemporary digital contract practices through the lens of classical Islamic jurisprudence, particularly the concepts of Ridā (mutual consent), Bayān (transparency), and Dafʿ al-Ḍarar (prevention of harm). A comparative analysis is also conducted of existing digital consumer protection regulations. Findings – The study finds that automatic renewal practices often contain elements of gharar yasir (minor uncertainty) that can escalate into gharar fahish (excessive uncertainty) when transparency is low. The reliance on passive consent and "dark patterns" in interface design often compromises the validity of Ridā. Furthermore, these mechanisms frequently lead to unintended financial charges, which contradict the Maqāṣid al-Sharīʿah principle of Ḥifẓ al-Māl (the protection of wealth). Implications – This study suggests that digital service providers should implement "Active Consent" models and clear notification intervals to ensure Shariah compliance. It also provides a framework for Islamic financial regulators to develop specific guidelines for subscription-based Fintech and digital commerce. Originality – While many studies discuss general e-commerce, this study provides a specialized Shariah critique of the "Subscription Economy" billing cycle, offering a novel integration of algorithmic transparency and Islamic contractual ethics.